ANALYSIS OF ACCEPTANCE OF ACCOUNTING INFORMATION SYSTEM IMPLEMENTATION BASED ON ELECTRONIC PAYMENT USING THE UTAUT MODEL - Aviyanti, Richo Diana; Saraswati, Erwin; Prastiwi, Arum (The International Journal of Accounting and Business Society, 2021)
Purpose —  Accounting is not only about the final result (financial statements) but also about the process towards the final result (system). The process will produce useful information as a guide for making decisions that are considered the most profitable. Often, this process is related to human behaviour because humans are both users and producers of information. Therefore, this study aims to examine and analyze the effect of performance expectancy, effort expectancy, social influences, and facilitating conditions on the actual use of electronic payment-based accounting information systems.Design/methodology/approach —  Data obtained through online questionnaires filled out by 247 active users of OVO electronic payment systems. The analysis method used is a structural equation regression model (Structural Equation Modeling/SEM) with a Partial Least Square/PLS test tool.Findings —  Empirical evidence shows that performance expectancy, effort expectancy, social influences, and facilitating condition significantly affect electronic payment systems' actual use.Practical implications — Electronic payment system service providers are advised to provide a useful system for meeting daily needs, complete transactions faster, and increase user performance and productivity. The study results show that consumers prefer electronic payment systems that are useful, time-saving, flexible, and increase productivity. Electronic payment system service providers are advised to provide a system that is easy to operate and easy to learn. The study results show that consumers prefer systems that are easy to operate, easy to learn, and easy to become skilled at when using them. Electronic payment system service providers are advised to provide electronic payment application systems that can be used by all types of devices, provide features that explain how to operate and continue to maximize their functions. The government is advised to also support the implementation of electronic payment systems by providing clear legal regulations on consumer protection and satellite internet networks. The results showed that accessing electronic payments requires the support of infrastructure, resources, and knowledge.Originality/value — The study results can add to the empirical evidence on sustainable use of electronic payment systems modeled directly against actual use. Electronic payment service providers must provide a system that is useful to meet needs, complete transactions faster, and improve system users' performance and productivity. Electronic payment service providers must provide a system that is easy to operate and easy to understand how to use. Electronic payment service providers can take advantage of the social environment to share information about the system's usability and convenience with potential users and users. Electronic payment service providers must add a brief and clear way of using the system, ensuring that electronic payment applications can be operated on all types of smartphones with maximum functionality. The government can help provide the infrastructure to support implementation and consumer security through regulation and internet network provision.Keywords —  Accounting; System; Electronic Payments; UTAUT; and Actual Use.Paper type —  Positive Paradigm Research Paper